Styl życia chorych z marskością wątroby zakażonych wirusem HCV = Life style of patients with cirrhosis infected with HCV virus - Lidia Sierpińska; Beata Wojtczak (Kazimierz Wielki University, 2016)
Sierpińska Lidia, Wojtczak Beata. Styl życia chorych z marskością wątroby zakażonych wirusem HCV = Life style of patients with cirrhosis infected with HCV virus. Journal of Education, Health and Sport. 2016;6(10):109-130. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.160477 http://ojs.ukw.edu.pl/index.php/johs/article/view/3928       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 12.10.2016.       Styl życia chorych z marskością wątroby zakażonych wirusem HCV Life style of patients with cirrhosis infected with HCV virus Lidia Sierpińska1, Beata Wojtczak2 1 1 Wojskowy Szpital Kliniczny z Polikliniką SP ZOZ w Lublinie 1 Military Clinical Hospital with Polyclinic, Independent Public Health Care Unit, Lublin   2 Studenckie Koło Naukowe Wyższej Szkoły Biznesu i Przedsiębiorczości w Ostrowcu Świętokrzyskim Students' Scientific Circle, College of Business and Entrepreneurship, Ostrowiec Świętokrzyski   Adres do korespondencji: dr n. med. Lidia Sierpińska 1 Wojskowy Szpital Kliniczny z Polikliniką SP ZOZ, Al. Racławickie 23, 20-904 Lublin, Poland tel. 261183297; fax. 261183277 e-mail: sierpinska1@wp.pl   Streszczenie Wprowadzenie. Marskość wątroby i pierwotny rak wątroby stanowią największe zagrożenie dla osób zakażonych wirusem HCV. Zdaniem naukowców antyzdrowotny styl życia przyspiesza proces włóknienia miąższu wątroby.  Cel. Rozpoznanie stylu życia chorych z pozapalną marskością wątroby z powodu zakażenia wirusem HCV Materiał i metoda. Badaniami objęto 104 osoby dorosłe - 43 mężczyzn i 61 kobiet       w wieku 36 - 55 i powyżej lat, hospitalizowanych w oddziale chorób wewnętrznych Powiatowego Centrum Medycznego w Grójcu. Badania przeprowadzono od marca do kwietnia 2016 roku. Metodą badawczą był sondaż diagnostyczny, zaś narzędziem - autorski kwestionariusz ankiety. Wyniki. Około ¾ badanych (72,1%) nie znało objawów pozapalnej marskości wątroby. U respondentów stwierdzono deficyt wiedzy odnośnie żywienia dietetycznego - "średni" poziom (54,8%), "niski" poziom (44,2%). "Czasami" przestrzegało dietę 48,1% badanych, "nie" przestrzegało diety 44,2% chorych. Liczna grupa badanych (42,3%) paliła papierosy. U ponad ½ badanych aktywność fizyczna uległa zmniejszeniu, a ¼ respondentów zaniechało aktywności fizycznej. Odpoczynek bierny preferowało 40,4% badanych, a 14,4% chorych nie miało czasu na odpoczynek. Znaczny odsetek badanych (79,3%) nie było narażonych na przewlekły stres, a dla pozostałych źródłem stresu były: warunki w pracy, atmosfera w rodzinie, objawy choroby. Wnioski. Chorym z pozapalną marskością wątroby z powodu zakażenia wirusem HCV należy poświęcać więcej czasu na edukację zdrowotną na temat: istoty choroby, zasad żywienia dietetycznego, eliminacji nałogu palenia papierosów, aktywności fizycznej.  W edukacji zdrowotnej chorych należy prezentować podmiotowe podejście, udzielać im wsparcia psychicznego z uwagi na narażenie na stres w miejscu pracy, atmosferę          w rodzinie i objawy choroby. Słowa kluczowe: pozapalna marskość wątroby, styl życia zakażonych HCV Abstract Introduction. Cirrhosis of the liver and hepatocellular carcinoma create the greatest risk for patients infected with HCV virus. According to the researchers anti-health life style accelerates the process of fibrosis of the hepatic parenchyma.   Objective. Recognition of the life style of patients with pro-inflammatory liver cirrhosis due to infection with HCV virus. Material and method. The study cover 104 adults - 43 males and 61 females aged 36 - 55 and over, hospitalized in the internal diseases ward at the Provincial Medical Centre in Grójec. The study was conducted during the period from March-April 2016, by the method of a diagnostic survey, using the technique of a questionnaire designed by the author. Results. Approximately ¾ of respondents (72.1%) did not know the symptoms of pro-inflammatory cirrhosis. The deficit of knowledge was also observed concerning dietetic nutrition - 'mediocre' level (54.8%), 'low' level' (44.2%); 48.1% of respondents observed diet 'sometimes', while 44.2% of patients did not observe diet at all. A large group of respondents (42.3%) smoked cigarettes. In more than a half of patients physical activity was reduced, whereas ¼ of them discontinued any physical activity; 40.4% of respondents preferred passive leisure, while 14.4% of patients had no time for rest. A considerable percentage of respondents (79.3%) were not exposed to chronic stress, whereas in the remainder the sources of stress were: work conditions, atmosphere in the family, and symptoms of the disease.  Conclusions. More time should be devoted to patients with pro-inflammatory cirrhosis due to HCV virus infection for health education concerning: the essence of the disease, principles of dietetic treatment, elimination of the cigarette smoking habit, and physical activity. In health education of patients a subjective approach should be represented, they should be provided psychological support considering the exposure to stress at work, atmosphere in the family, and symptoms of the disease.  Key words: pro-inflammatory liver cirrhosis, life style of patients infected with HCV